Plasma Proteomic Profiling Reveals ITGA2B as A Key Regulator of Heart Health in High-altitude Settlers - Wang (王一豪), Yihao; Shen (沈磐), Pan; Wu (伍振辉), Zhenhui; Tu (涂博丹), Bodan; Zhang (张程), Cheng; Zhou (周永强), Yongqiang; Liu (刘溢思), Yisi; Wang (王贵宾), Guibin; Bai (柏志杰), Zhijie; Tang (汤响林), Xianglin; Lai (赖成材), Chengcai; Lu (吕海涛), Haitao; et al. (Genomics, proteomics & bioinformatics, 2025)
Myocardial injury is a common disease in the plateau, especially in the lowlanders who have migrated to the plateau, in which the pathogenesis is not well understood. Here, we established a cohort of lowlanders comprising individuals from both low-altitude and high-altitude areas and conducted plasma proteomic profiling. Proteomic data showed that there was a significant shift in energy metabolism and inflammatory response in individuals with myocardial abnormalities at high altitude. Notably, integrin alpha-Ⅱb (ITGA2B) emerged as a potential key player in this context. Functional studies demonstrated that ITGA2B upregulated the transcription and secretion of interleukin-6 (IL-6) through the integrin-linked kinase (ILK)/nuclear factor-κB (NF-κB) signaling axis under hypoxic conditions. Moreover, ITGA2B disrupted mitochondrial structure and function, increased glycolytic capacity, and aggravated energy reprogramming from oxidative phosphorylation to glycolysis. Leveraging the therapeutic potential of traditional Chinese medicine in cardiac diseases, we discovered that tanshinone ⅡA (TanⅡA) effectively alleviated the myocardial injury caused by the abnormally elevated expression of ITGA2B and hypobaric hypoxia exposure in mice, thus providing a novel candidate therapeutic strategy for the prevention and treatment of high-altitude myocardial injury.